Express the following in partial fraction and hence differentiate

Y=3x_1/(x+2)(2x_1)

2 answers

(3x-1)/((x+2)(2x-1)) = A/(x+2) + B/(2x-1)
3x-1 = A(2x-1) + B(x+2)
so
2A+B = 3
-A+2B = -1
solve for A and B
or, once you get to oobleck's 3x-1 = A(2x-1) + B(x+2)
let x = -2 ----> -7 = -5A + 0 , A = 7/5
let x = 1/2 ---> 1/2 = 0 + 5/2 B, B = 1/5
Similar Questions
  1. Express in simplest form: 36x−216x2−36 .(1 point)Responses 36x−6 Start Fraction 36 over x minus 6 End Fraction 6x Start
    1. answers icon 1 answer
    1. answers icon 3 answers
  2. Express the following fraction in lowest terms.start fraction 18 over 42 end fraction (1 point) Responses start fraction 9 over
    1. answers icon 3 answers
    1. answers icon 2 answers
more similar questions